GAMBARAN STRATIFIKASI SOSIAL DALAM CERITA PENDEK THE SLEEPING BEAUTY IN THE WOOD KARYA CHARLES PERRAULT - SINGKARA, FRANCHOYNESTTU EFRANA SALLOMO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Short story is a piece of prose fiction. Short story features a small cast of named characters, and focuses on a